CHARACTER EDUCATION COMPARISON OF PRIMARY SCHOOL STUDENTS IN INDONESIA AND JAPAN - Ellyana Hinta, Dakia Djou, Asna Ntelu, Mira Mirnawati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper aims to describe and to compare character education of primary school students both in Indonesia and Japan. This study used a qualitative descriptive analysis for its methodology. The findings indicated that Indonesian curriculum comprises six learning subjects along with mathematical calculation and memorization for first to third grade students of primary school, while Japan curriculum does not provide mathematical calculation and memorization for these grades. Other than that, Indonesia enforces character education in two areas, i.e., schools and families, while Japan incorporates the character education in three fields, i.e., schools, families, and communities. In addition, Indonesia have formulated eighteen pillars of character education, while Japan provides twenty-four pillars. Indonesia character education could be developed by emulating the success of character education in Japan.